A method for treating sulfate-containing wastewater

CN122831497APending Publication Date: 2026-09-29ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610951182.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

但传统利用铝盐和/或钙盐来降低含硫酸根废水中硫酸根含量的方法,硫酸根去除率较低

Benefits of technology

本申请的含硫酸根废水的处理方法,先向待处理的含硫酸根废水中加入钙源进行第一反应,将硫酸根沉淀为硫酸钙,得到第一水体(第一水体中的硫酸根含量明显少于含硫酸根废水中硫酸根含量)。再向第一水体中加入复合稀土铝胶体进行第二反应,复合稀土铝胶体由稀土离子(水溶性稀土盐提供稀土离子)与铝源在pH 5.5~6.5条件下进行共水解反应,使稀土离子以羟基架桥或晶格共聚形式嵌入铝羟基聚合网络,形成稳定的复合稀土铝胶体。复合稀土铝胶体中的稀土离子对阴离子(例如硫酸根)具有强亲和力,稀土离子与硫酸根在pH为9.0~12.0的条件下,通过离子键和配位键发生化学结合,促使稀土离子与硫酸根通过晶格共沉淀方式生成稳定的碱式硫酸稀土复盐沉淀物,同时,复合稀土铝胶体中的铝羟基聚合网络通过架桥与网捕作用,将上述沉淀物快速聚集为粗大絮体,从而实现硫酸根从液相中的深度分离。再向完成第二反应后的混合体系中加入絮凝剂,快速将生成的硫酸钙、碱式硫酸稀土复盐沉淀物及粗大絮体团聚为大颗粒絮团,固液分离得到回用水,硫酸根去除率可达90%以上。本申请的含硫酸根废水的处理方法操作简便、设备简单、处理成本低,硫酸根去除率高,适用于矿山、化工等行业高浓度硫酸根废水的处理。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122831497A_ABST
    Figure CN122831497A_ABST
Patent Text Reader

Abstract

The application discloses a treatment method of sulfate-containing wastewater, comprising the following steps: mixing a water-soluble rare earth salt and an aluminum source in water, and performing a co-hydrolysis reaction under the condition that the pH of a reaction system is 5.5-6.5 to obtain a composite rare earth aluminum colloid; adding a calcium source into the sulfate-containing wastewater to be treated to perform a first reaction, and controlling the pH of the reaction system of the first reaction to be 9.0-12.0 to obtain a first water body; adding the composite rare earth aluminum colloid into the first water body to perform a second reaction; and adding a flocculating agent into the mixed system after the second reaction to perform flocculation and sedimentation, and performing solid-liquid separation to obtain recycled water. The sulfate removal rate of the method can reach more than 90 %.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of industrial wastewater treatment technology, and in particular to a method for treating sulfate-containing wastewater. Background Technology

[0002] With the rapid development of the alumina industry both domestically and internationally, high-grade bauxite is becoming increasingly scarce, while low-grade bauxite is flooding the market. High-sulfur bauxite, in particular, poses a significant threat to production due to its high sulfur content, making it difficult to process economically using the traditional Bayer process. Developing and utilizing domestically sourced, complex, and difficult-to-process high-sulfur bauxite resources for the alumina industry can extend the service life of my country's bauxite reserves. Reverse flotation desulfurization is a relatively economical and effective method for high-sulfur bauxite. However, the repeated recycling of circulating water during reverse flotation desulfurization leads to sulfate enrichment, affecting the grade of the alumina concentrate produced and resulting in a higher sulfur content, thus impacting the alumina production process.

[0003] In the field of water treatment, aluminum and calcium salts are commonly used and inexpensive agents in industrial wastewater treatment. Aluminum salts can form aluminum hydroxide colloids, enhancing adsorption and flocculation effects, while calcium salts can react with sulfate ions to form calcium sulfate precipitates, thus capturing sulfate ions. However, traditional methods of using aluminum and / or calcium salts to reduce the sulfate content in sulfate-containing wastewater have relatively low sulfate removal rates. Summary of the Invention

[0004] The method for treating sulfate-containing wastewater according to one or more embodiments of this application solves one of the technical problems of low sulfate removal rate.

[0005] A first aspect of this application provides a method for treating sulfate-containing wastewater, comprising the following steps: mixing water-soluble rare earth salts and an aluminum source in water, and performing a co-hydrolysis reaction under the condition that the pH of the reaction system is 5.5~6.5 to obtain a composite rare earth aluminum colloid; adding a calcium source to the sulfate-containing wastewater to be treated to carry out a first reaction, and controlling the pH of the reaction system of the first reaction to be 9.0~12.0 to obtain a first water body; adding the composite rare earth aluminum colloid to the first water body to carry out a second reaction; and adding a flocculant to the mixed system after the second reaction to carry out flocculation and sedimentation, and solid-liquid separation to obtain recycled water.

[0006] Optionally, the water-soluble rare earth salt includes rare earth chloride salts and / or rare earth nitrate salts, and the aluminum source includes water-soluble aluminum monomer salts and / or polyaluminum compounds; and / or, The molar ratio of rare earth ions in the water-soluble rare earth salt to aluminum in the aluminum source is 1:(2~4).

[0007] Optionally, the rare earth ions in the water-soluble rare earth salt include one or more of yttrium, lanthanum, cerium, neodymium, and gadolinium.

[0008] Optionally, the aluminum source includes aluminum chloride and / or polyaluminum chloride.

[0009] Optionally, the calcium source includes one or more of calcium chloride, calcium oxide, and calcium hydroxide; and / or, The molar ratio of calcium in the calcium source to sulfate in the sulfate-containing wastewater is (1.0~1.7):1.

[0010] Optionally, the molar ratio of rare earth ions in the composite rare earth aluminum colloid to sulfate ions in the first water body is (1~1.5):1.

[0011] Optionally, the flocculant includes anionic polyacrylamide flocculants, and / or, Based on the volume of the mixed system, the dosage of the flocculant is 1 mg / L to 2 mg / L.

[0012] Optionally, the anionic polyacrylamide flocculant has a molecular weight of 8 million to 12 million and a degree of hydrolysis of 20% to 30%.

[0013] Optionally, the first reaction is carried out at a stirring speed of 200 r / min to 300 r / min for 5 to 10 minutes; and / or, The second reaction is carried out at a stirring speed of 150 r / min to 200 r / min for 10 to 15 minutes; and / or, The flocculation and sedimentation process involves stirring for 3 to 5 minutes at a stirring speed of 100 r / min to 200 r / min, followed by settling for 30 to 60 minutes.

[0014] Optionally, the concentration of sulfate in the sulfate-containing wastewater is 1000 mg / L to 10000 mg / L.

[0015] Compared with the prior art, the technical solution provided in this application has the following beneficial effects: The method for treating sulfate-containing wastewater disclosed in this application involves first adding a calcium source to the sulfate-containing wastewater to initiate a first reaction, precipitating sulfate ions into calcium sulfate, resulting in a first water body (the sulfate content in the first water body is significantly lower than that in the sulfate-containing wastewater). Then, a composite rare-earth aluminum colloid is added to the first water body for a second reaction. The composite rare-earth aluminum colloid is formed by the co-hydrolysis reaction of rare-earth ions (provided by water-soluble rare-earth salts) and an aluminum source under pH conditions of 5.5–6.5, allowing the rare-earth ions to embed into the aluminum hydroxyl polymer network in the form of hydroxyl bridging or lattice copolymerization, thus forming a stable composite rare-earth aluminum colloid. The rare earth ions in the composite rare earth aluminum colloid have a strong affinity for anions (such as sulfate). Under pH conditions of 9.0~12.0, rare earth ions and sulfate undergo chemical bonding through ionic and coordinate bonds, promoting the formation of stable basic rare earth sulfate double salt precipitates through lattice co-precipitation. Simultaneously, the aluminum hydroxyl polymer network in the composite rare earth aluminum colloid rapidly aggregates the above precipitates into coarse flocs through bridging and entrapment, thereby achieving deep separation of sulfate from the liquid phase. A flocculant is then added to the mixed system after the second reaction, rapidly agglomerating the generated calcium sulfate, basic rare earth sulfate double salt precipitates, and coarse flocs into large flocs. Solid-liquid separation yields recycled water, with a sulfate removal rate exceeding 90%. The sulfate-containing wastewater treatment method of this application is simple to operate, uses simple equipment, has low treatment costs, and achieves a high sulfate removal rate, making it suitable for treating high-concentration sulfate wastewater in mining, chemical, and other industries.

[0016] The method for treating sulfate-containing wastewater described in this application has broad applicability to complex water quality (containing high concentrations of sulfate) caused by pyrite oxidation in the desulfurization circulating water of high-sulfur bauxite reverse flotation, and is easy to implement industrially. Attached Figure Description

[0017] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and disclosure, and together with the description serve to explain the principles of this application and disclosure.

[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a schematic flowchart of a method for treating sulfate-containing wastewater according to some embodiments of this application. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0021] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. The term "implementation" as used herein has a similar understanding.

[0022] In this application, except where expressly stated, any matters or issues not mentioned are directly applicable to those known in the art without any modification. Furthermore, any implementation described in this application can be freely combined with one or more other implementations described in this application, and the resulting technical solutions or concepts shall be considered part of the original disclosure or original record of this application, and should not be regarded as new content not disclosed or anticipated in this application, unless those skilled in the art consider the combination to be clearly unreasonable.

[0023] Any method steps, processes, and operations described in this application should not be construed as necessarily requiring them to be performed in a particular order as discussed or shown, unless explicitly specified. It should also be understood that additional or alternative steps may be used unless otherwise stated.

[0024] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0025] Any specific numerical values ​​disclosed herein (including the endpoints of numerical ranges) are not limited to their exact values, but should be understood to also include values ​​close to the exact value, such as all possible values ​​within ±5% of the exact value. Furthermore, with respect to the disclosed numerical ranges, one or more new numerical ranges can be obtained by arbitrarily combining the endpoint values ​​of the range, the endpoint values ​​with specific point values ​​within the range, and the specific point values ​​themselves; these new numerical ranges should also be considered as specifically disclosed herein.

[0026] Unless otherwise stated, the terms used herein have the same meaning as commonly understood by those skilled in the art, and if a term is defined herein and its definition differs from the common understanding in the art, the definition herein shall prevail.

[0027] In this article, "sulfate" refers to "SO4²⁻". - ".

[0028] Unless otherwise specified, all reactions in this article were carried out at room temperature (20℃~25℃).

[0029] In this document, "high-sulfur bauxite" refers to bauxite with a total sulfur mass fraction (calculated as elemental S) ≥ 0.8%. Preferably, the total sulfur mass fraction in the high-sulfur bauxite is 3.0%~6.0%, more preferably, it is 6.0%~10.0%. The sulfur in the high-sulfur bauxite mainly exists in the form of pyrite (FeS2). During the reverse flotation desulfurization process, the pyrite undergoes oxidation and the action of beneficiation reagents, resulting in a high concentration of sulfate ions accumulating in the flotation circulating water.

[0030] First aspect Please see Figure 1 This application provides a method for treating sulfate-containing wastewater, comprising the following steps: S1, water-soluble rare earth salt and aluminum source are mixed in water and co-hydrolyzed under the condition that the pH of the reaction system is 5.5~6.5 to obtain composite rare earth aluminum colloid; S2, a calcium source is added to the sulfate-containing wastewater to be treated to carry out the first reaction, and the pH of the reaction system is controlled at 9.0~12.0 to obtain the first water body; S3, the composite rare earth aluminum colloid is added to the first water body to carry out a second reaction; and S4. Add flocculant to the mixed system after the second reaction to carry out flocculation and sedimentation, solid-liquid separation, and obtain recycled water.

[0031] The method for treating sulfate-containing wastewater according to this application embodiment first involves adding a calcium source to the sulfate-containing wastewater to undergo a first reaction, precipitating sulfate ions into calcium sulfate, resulting in a first water body (the sulfate content in the first water body is significantly lower than that in the sulfate-containing wastewater). Then, a composite rare-earth aluminum colloid is added to the first water body for a second reaction. The composite rare-earth aluminum colloid is formed by the co-hydrolysis reaction of rare-earth ions (provided by water-soluble rare-earth salts) and an aluminum source under pH conditions of 5.5-6.5, allowing the rare-earth ions to embed into the aluminum hydroxyl polymer network in the form of hydroxyl bridging or lattice copolymerization, thus forming a stable composite rare-earth aluminum colloid. The rare earth ions in the composite rare earth aluminum colloid have a strong affinity for anions (such as sulfate). Under conditions of pH 9.0~12.0, rare earth ions and sulfate undergo chemical bonding through ionic and coordinate bonds, promoting the formation of stable basic rare earth sulfate double salt precipitates through lattice co-precipitation. Simultaneously, the aluminum hydroxyl polymer network in the composite rare earth aluminum colloid rapidly aggregates the above precipitates into coarse flocs through bridging and entrapment, thereby achieving deep separation of sulfate from the liquid phase. Adding a flocculant to the mixture after the second reaction quickly agglomerates the generated calcium sulfate, basic rare earth sulfate double salt precipitates, and coarse flocs into large flocs, resulting in solid-liquid separation and recycled water. The sulfate removal rate can reach over 90%.

[0032] It should be noted that the mechanism by which rare earth ions in composite rare earth aluminum colloids are embedded in the aluminum hydroxyl polymer network of aluminum in the form of hydroxyl bridging or lattice copolymerization is as follows: Aluminum source is hydrolyzed to provide polynuclear hydroxyl aluminum ions. Adjacent polynuclear hydroxyl aluminum ions continuously crosslink and extend through hydroxyl bridging reactions (hydroxyl crosslinking), assembling into an aluminum hydroxyl polymer network with a three-dimensional spatial structure. This network contains a large number of highly active hydroxyl (-OH) groups. During this process, rare earth ions are anchored in situ into the framework structure of this aluminum hydroxyl polymer network through hydroxyl crosslinking or lattice copolymerization, thereby forming a composite rare earth aluminum colloid with aluminum as the framework and rare earth as the active center.

[0033] In this application, the copolymerization of rare earth salts and aluminum sources at pH 5.5–6.5 is not a simple coexistence of ions, but rather a copolymerization of rare earth ions (RE³). + By embedding itself into the aluminum hydroxyl polymer network of aluminum through hydroxyl bridging, a multi-hydroxyl complex colloid with a specific stoichiometric ratio is formed. The rare earth ions in this colloid are "anchored" by the aluminum hydroxyl polymer network, thereby avoiding the failure of rare earth elements to hydrolyze alone in the subsequent treatment of high pH (9~12) wastewater, and significantly improving the effective utilization rate of rare earth elements.

[0034] In some embodiments, the aluminum source comprises water-soluble aluminum monomer salts and / or polyaluminum compounds. In some alternative embodiments, the aluminum source comprises aluminum chloride and / or polyaluminum chloride. Polyaluminum chloride, abbreviated as PAC, has the chemical formula […]. (in , It is an inorganic polymer. When the aluminum source contains PAC, the number of moles of aluminum is calculated based on the mass percentage of alumina (Al2O3) indicated on the PAC product (e.g., 28%~32%). The conversion formula is: Number of moles of aluminum (Al) = [PAC mass (g) × Al2O3 content (%)] / 102 × 2. For example, when using PAC with an Al2O3 content of 30%, the number of moles of aluminum contained in 1 gram of this PAC is 1g × 30% ÷ 102 × 2 ≈ 0.00588 mol.

[0035] It should be noted that water-soluble aluminum monomer salts refer to those that exist in water as free Al³⁺. + Non-polymerized aluminum salts (such as aluminum chloride, aluminum nitrate, and aluminum sulfate) exist in a physical form, distinct from polymerized aluminum compounds. Polymeric aluminum compounds are inorganic polymers with multinuclear hydroxyl-bridged complex structures formed by the partial neutralization (addition of alkali) of aluminum salts (such as aluminum chloride and aluminum sulfate) through hydroxyl (-OH) bridging. They are not simple Al... 3+ Aluminum chloride is not an ion, but a large molecular aggregate composed of several to dozens of aluminum atoms linked by oxygen bridges or hydroxyl bridges. Its main body is a network of polynuclear hydroxyl aluminum ions. Water-soluble aluminum monomer salts, such as aluminum chloride, first form hydrated aluminum ions when dissolved in water. At pH 5.5–6.5, the hydrated aluminum ions begin to lose protons from water molecules. ), generating hydroxyl ligands ( These hydroxyl ligands act as "bridges" between different aluminum ions, connecting multiple aluminum ions through hydroxyl bridging reactions to form an aluminum hydroxyl polymer network. Polyaluminum compounds (such as PAC) themselves possess an aluminum hydroxyl polymer network, undergoing a reversible hydrolysis-condensation dynamic equilibrium (Al-OH-Al + H2O) with the participation of water molecules. 2Al-OH). Under pH conditions of 5.5-6.5, the hydrolysis equilibrium shifts moderately towards the chain breakage direction, exposing a large number of active hydroxyl coordination sites. Rare earth ions chemically coordinate and intercalate with these exposed active hydroxyl groups, anchoring the rare earth ions within the reorganized aluminum hydroxyl network framework through new hydroxyl bridges (Al-O-rare earth ions).

[0036] Although rare earth ions have a strong affinity for anions, the direct addition of water-soluble rare earth salts under alkaline conditions easily leads to rapid hydrolysis, forming rare earth hydroxide precipitates, which reduces the effective utilization rate of rare earth ions and results in unstable sulfate removal. This application, however, avoids the failure of rare earth ions due to hydrolysis alone by utilizing molecular-level copolymerization of rare earth ions and aluminum hydrolysis polymers. The composite rare earth aluminum colloid provided by this application has rare earth ions firmly bound within the aluminum hydroxyl network framework, greatly improving the stability of the rare earth ions.

[0037] In some embodiments, water-soluble rare earth salts include rare earth chlorides and / or rare earth nitrates. In some embodiments, the rare earth ions in the water-soluble rare earth salt include one or more of yttrium, lanthanum, cerium, neodymium, and gadolinium.

[0038] It should be noted that water-soluble rare earth salts refer to rare earth inorganic or organic acid salts with a solubility of not less than 10 g / L in water at 20°C, including but not limited to rare earth nitrates (such as yttrium nitrate hexahydrate, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, neodymium nitrate hexahydrate, or gadolinium nitrate hexahydrate, etc.) and rare earth chlorides (such as anhydrous lanthanum chloride, hydrated lanthanum chloride, yttrium chloride, etc.). Preferably, the water-soluble rare earth salt is gadolinium nitrate hexahydrate (Gd(NO3)3·6H2O).

[0039] Nitrate ions (NO3) - ) and chloride ions (Cl - Both nitrate and chloride ions are typical soluble co-occurring anions. Under the second reaction conditions, neither nitrate nor chloride ions react with calcium, rare earth, or aluminum ions to form a precipitation reaction, nor do they embed into the crystal lattice of basic rare earth sulfate double salt precipitates. However, given the potential pitting corrosion risk of chloride ions on stainless steel equipment in high-sulfur, high-alkali slurry environments, this application prefers nitrate ions as co-occurring anions for water-soluble rare earth salts when treating desulfurization circulating water from high-sulfur bauxite reverse flotation. In the recycled water treated by this application, residual nitrate ions can be naturally consumed through subsequent conventional reverse flotation operations (e.g., as slurry electrolytes) or discharged with the final tailings, without accumulating in the closed-loop circulation, and without affecting the reagent efficacy and concentrate indicators of bauxite reverse flotation desulfurization. Therefore, this application uses rare earth nitrates as water-soluble rare earth salts to achieve efficient removal of sulfate ions without introducing new difficult-to-treat pollutants, and it has better equipment compatibility compared to chloride systems.

[0040] In some embodiments, the molar ratio of rare earth ions in the water-soluble rare earth salt to aluminum in the aluminum source is 1:(2~4). For example, the molar ratio of rare earth ions in the water-soluble rare earth salt to aluminum in the aluminum source is 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.

[0041] In step S1, the pH of the reaction system can be adjusted to 5.5-6.5 using a pH adjuster. The pH adjuster may include, but is not limited to, one or more of sodium hydroxide, potassium hydroxide, and calcium hydroxide.

[0042] In some implementations, the calcium source includes one or more of calcium chloride, calcium oxide, and calcium hydroxide.

[0043] In some embodiments, the molar ratio of calcium in the calcium source to sulfate in the sulfate-containing wastewater is (1.0~1.7):1. For example, the molar ratio of calcium in the calcium source to sulfate in the sulfate-containing wastewater is 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1 or 1.7:1.

[0044] In some embodiments, the calcium source includes calcium hydroxide, eliminating the need for additional pH adjusters during the first reaction. The pH of the reaction system can be controlled to be 9.0–12.0 using calcium hydroxide's own alkalinity. Using calcium hydroxide as the calcium source simplifies the operation and avoids introducing other ions that could interfere with subsequent reactions.

[0045] It should be noted that controlling the pH of the reaction system in the first reaction to be 9.0~12.0 means maintaining the reaction system within this pH range throughout the entire first reaction. The control method is not limited; it can be achieved by adding an excess of calcium hydroxide or calcium oxide at once, utilizing its solid buffering effect to maintain pH stability; or it can be achieved by dynamically adjusting the pH value in real time during the reaction and supplementing with a calcium source and / or pH adjuster. The supplementation of the calcium source and / or pH adjuster can be precisely controlled using an automatic dosing system linked to an online pH meter. As long as the pH of the system falls within the range of 9.0~12.0 at the end of the first reaction and during the reaction process, it falls within the scope of protection of this application.

[0046] The reaction system for the first reaction refers to the mixed slurry system containing calcium source, precipitate, and sulfate-containing wastewater when a calcium source is added and a precipitation reaction occurs. The pH value of this mixed slurry is the pH value of the liquid phase (i.e., the first water body obtained after subsequent solid-liquid separation) under the reaction conditions. Controlling the pH of the reaction system for the first reaction to be between 9.0 and 12.0 is equivalent to controlling the pH of the first water body obtained after the first reaction to be within this target range. Controlling the pH of the first water body to be between 9.0 and 12.0 can induce the co-precipitation of rare earth ions and sulfate (i.e., induce the occurrence of the second reaction) and reduce the solubility of calcium sulfate.

[0047] In some embodiments, the molar ratio of rare earth ions in the composite rare earth aluminum colloid to sulfate ions in the first water body is (1~1.5):1. For example, the molar ratio of rare earth ions in the composite rare earth aluminum colloid to sulfate ions in the first water body is 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1.

[0048] In some embodiments, the flocculant includes one or more of polyaluminum chloride flocculant, polyferric sulfate flocculant, and polyacrylamide flocculant. In some alternative embodiments, the flocculant includes anionic polyacrylamide flocculant. Anionic polyacrylamide flocculant is intended to further improve the flocculation and sedimentation rate and solid-liquid separation efficiency, thereby improving sulfate removal efficiency.

[0049] In some embodiments, the anionic polyacrylamide flocculant has a molecular weight of 8 million to 12 million and a degree of hydrolysis of 20% to 30%. The degree of hydrolysis of anionic polyacrylamide flocculant refers to the percentage of sodium acrylate units (sodium carboxylate groups, i.e., anionic groups) in the total number of monomer units in the molecular chain. For example, a degree of hydrolysis of 25% for anionic polyacrylamide flocculant means that in this long molecular chain, out of every 100 structural units, 25 are negatively charged sodium carboxylate groups and 75 are neutral amide groups.

[0050] In some implementations, the flocculant dosage is 1 mg / L to 2 mg / L, based on the volume of the mixed system. For example, the flocculant dosage is 1 mg / L, 1.2 mg / L, 1.4 mg / L, 1.6 mg / L, 1.8 mg / L, or 2 mg / L, based on the volume of the mixed system.

[0051] In some embodiments, the first reaction is carried out at a stirring speed of 200 r / min to 300 r / min for 5 to 10 minutes. For example, the stirring speed of the first reaction is 200 r / min, 220 r / min, 250 r / min, 280 r / min or 300 r / min, and the reaction time of the first reaction is 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes.

[0052] In some embodiments, a solid-liquid separation step is included after the first reaction. In some embodiments, solid-liquid separation is performed by static precipitation, and the static precipitation time may be 25 min, 30 min, or 35 min.

[0053] In some embodiments, the second reaction is carried out at a stirring speed of 150 r / min to 200 r / min for 10 to 15 minutes. Exemplarily, the stirring speed of the second reaction is 150 r / min, 160 r / min, 180 r / min, 190 r / min, or 200 r / min, and the reaction time is 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, or 15 minutes.

[0054] In some embodiments, flocculation and sedimentation are carried out by stirring at a stirring speed of 100 r / min to 200 r / min for 3 to 5 minutes, followed by settling for 30 to 60 minutes. Exemplarily, the stirring speed for flocculation and sedimentation is 100 r / min, 120 r / min, 140 r / min, 160 r / min, 180 r / min, or 200 r / min; the stirring time is 3 minutes, 3.5 minutes, 4 minutes, 4.5 minutes, or 5 minutes; and the settling time is 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, or 60 minutes.

[0055] In some embodiments, the concentration of sulfate in the sulfate-containing wastewater is 1000 mg / L to 10000 mg / L. The sulfate concentration in the sulfate-containing wastewater is 1000 mg / L, 2000 mg / L, 3000 mg / L, 4000 mg / L, 5000 mg / L, 6000 mg / L, 7000 mg / L, 8000 mg / L, 9000 mg / L, or 10000 mg / L.

[0056] Example To better understand this application, the following description, in conjunction with embodiments, further illustrates this application. However, the scope of protection claimed in this application is not limited to the scope of the embodiments.

[0057] In the following examples, unless otherwise specified, all experimental instruments, raw materials, and quantities involved are commercially available products or can be prepared by known methods. Experimental methods not specifying particular conditions in the examples were performed under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.

[0058] Unless otherwise specified, the specific parameters used in each step of the material preparation process in each embodiment and comparative example are the same.

[0059] Example 1 The sulfate-containing wastewater to be treated is desulfurization wastewater from reverse flotation of a bauxite mine. The influent sulfate concentration is 6000 mg / L, and the pH is 5.2.

[0060] S1, according to the molar ratio of rare earth ions to aluminum element of 1:3, weigh yttrium nitrate hexahydrate (Y(NO3)3·6H2O, industrial grade) and polyaluminum chloride (PAC, Al2O3 content 30%, industrial grade), dissolve in water, add pH adjuster to adjust pH to 6.0, stir evenly to form composite rare earth aluminum colloid.

[0061] S2, with a calcium to sulfate molar ratio of approximately 1.62:1, 7.5 g of Ca(OH)2 was added to each liter of wastewater to initiate the first reaction. The pH of the reaction system naturally rose to 11.0. The mixture was stirred at 250 r / min for 10 min and then allowed to settle for 30 min. The effluent was the first water body, and the sulfate concentration in the first water body was measured to be 2200 mg / L.

[0062] S3, Add the composite rare earth aluminum colloid prepared in step S1 to the first water body to carry out the second reaction, and stir at 180 r / min for 10 min.

[0063] S4. Anionic polyacrylamide flocculant was added to the mixture after the second reaction to aid sedimentation. Based on the volume of the mixture, the flocculant dosage was 1.5 mg / L. The mixture was stirred at 100 r / min for 5 min and allowed to stand for 30 min. The supernatant was analyzed, and the sulfate concentration was 135 mg / L, with a sulfate removal rate of 97.75%.

[0064] Example 2 The procedure is essentially the same as in Example 1, except that yttrium nitrate hexahydrate (Y(NO3)3·6H2O, industrial grade) is replaced with lanthanum nitrate hexahydrate (La(NO3)3·6H2O, industrial grade). The specific steps are as follows: S1, according to the molar ratio of rare earth ions to aluminum elements of 1:3, weigh lanthanum nitrate hexahydrate (La(NO3)3·6H2O, industrial grade) and polyaluminum chloride (PAC, Al2O3 content 30%, industrial grade), dissolve them in water, add pH adjuster to adjust pH to 6.0, stir evenly to form composite rare earth aluminum colloid.

[0065] S2, with a calcium to sulfate molar ratio of approximately 1.62:1, 7.5 g of Ca(OH)2 was added to each liter of wastewater to initiate the first reaction. The pH of the reaction system naturally rose to 11.0. The mixture was stirred at 250 r / min for 10 min and then allowed to settle for 30 min. The effluent was the first water body, and the sulfate concentration in the first water body was measured to be 2200 mg / L.

[0066] S3, Add the composite rare earth aluminum colloid prepared in step S1 to the first water body to carry out the second reaction, and stir at 180 r / min for 10 min.

[0067] S4. Anionic polyacrylamide flocculant was added to the mixture after the second reaction to aid sedimentation. Based on the volume of the mixture, the flocculant dosage was 1.5 mg / L. The mixture was stirred at 100 r / min for 5 min and then allowed to stand for 30 min. The supernatant was analyzed, and the sulfate concentration was 176 mg / L, with a sulfate removal rate of 97.06%.

[0068] Example 3 The procedure is essentially the same as in Example 1, except that yttrium nitrate hexahydrate (Y(NO3)3·6H2O, industrial grade) is replaced with cerium nitrate hexahydrate (Ce(NO3)3·6H2O, industrial grade). The specific steps are as follows: S1, according to the molar ratio of rare earth ions to aluminum element of 1:3, weigh cerium nitrate hexahydrate (Ce(NO3)3·6H2O, industrial grade) and polyaluminum chloride (PAC, Al2O3 content 30%, industrial grade), dissolve in water, add pH adjuster to adjust pH to 6.0, stir evenly to form composite rare earth aluminum colloid.

[0069] S2, with a calcium to sulfate molar ratio of approximately 1.62:1, 7.5 g of Ca(OH)2 was added to each liter of wastewater to initiate the first reaction. The pH of the reaction system naturally rose to 11.0. The mixture was stirred at 250 r / min for 10 min and then allowed to settle for 30 min. The effluent was the first water body, and the sulfate concentration in the first water body was measured to be 2200 mg / L.

[0070] S3, Add the composite rare earth aluminum colloid prepared in step S1 to the first water body to carry out the second reaction, and stir at 180 r / min for 10 min.

[0071] S4. Anionic polyacrylamide flocculant was added to the mixture after the second reaction to aid sedimentation. Based on the volume of the mixture, the flocculant dosage was 1.5 mg / L. The mixture was stirred at 100 r / min for 5 min and allowed to stand for 30 min. The supernatant was analyzed, and the sulfate concentration was 458 mg / L, with a sulfate removal rate of 92.37%.

[0072] Example 4 The process is basically the same as in Example 1, except that yttrium nitrate hexahydrate (Y(NO3)3·6H2O, industrial grade) is replaced with neodymium nitrate hexahydrate (Nd(NO3)3·6H2O, industrial grade). The specific steps are as follows: S1, according to the molar ratio of rare earth ions to aluminum elements of 1:3, weigh neodymium nitrate hexahydrate (Nd(NO3)3·6H2O, industrial grade) and polyaluminum chloride (PAC, Al2O3 content 30%, industrial grade), dissolve in water, add pH adjuster to adjust pH to 6.0, stir evenly to form composite rare earth aluminum colloid.

[0073] S2, with a calcium to sulfate molar ratio of approximately 1.62:1, 7.5 g of Ca(OH)2 was added to each liter of wastewater to initiate the first reaction. The pH of the reaction system naturally rose to 11.0. The mixture was stirred at 250 r / min for 10 min and then allowed to settle for 30 min. The effluent was the first water body, and the sulfate concentration in the first water body was measured to be 2200 mg / L.

[0074] S3, Add the composite rare earth aluminum colloid prepared in step S1 to the first water body to carry out the second reaction, and stir at 180 r / min for 10 min.

[0075] S4. Anionic polyacrylamide flocculant was added to the mixture after the second reaction to aid sedimentation. Based on the volume of the mixture, the flocculant dosage was 1.5 mg / L. The mixture was stirred at 100 r / min for 5 min and then allowed to stand for 30 min. The supernatant was analyzed, and the sulfate concentration was 235 mg / L, with a sulfate removal rate of 96.08%.

[0076] Example 5 The procedure is basically the same as in Example 1, except that yttrium nitrate hexahydrate (Y(NO3)3·6H2O, industrial grade) is replaced with gadolinium nitrate hexahydrate (Gd(NO3)3·6H2O, industrial grade). The specific steps are as follows: S1, according to the molar ratio of rare earth ions to aluminum element of 1:3, weigh gadolinium nitrate hexahydrate (Gd(NO3)3·6H2O, industrial grade) and polyaluminum chloride (PAC, Al2O3 content 30%, industrial grade), dissolve in water, add pH adjuster to adjust pH to 6.0, stir evenly to form composite rare earth aluminum colloid.

[0077] S2, with a calcium to sulfate molar ratio of approximately 1.62:1, 7.5 g of Ca(OH)2 was added to each liter of wastewater to initiate the first reaction. The pH of the reaction system naturally rose to 11.0. The mixture was stirred at 250 r / min for 10 min and then allowed to settle for 30 min. The effluent was the first water body, and the sulfate concentration in the first water body was measured to be 2200 mg / L.

[0078] S3, Add the composite rare earth aluminum colloid prepared in step S1 to the first water body to carry out the second reaction, and stir at 180 r / min for 10 min.

[0079] S4. Anionic polyacrylamide flocculant was added to the mixture after the second reaction to aid sedimentation. Based on the volume of the mixture, the flocculant dosage was 1.5 mg / L. The mixture was stirred at 100 r / min for 5 min and allowed to stand for 30 min. The supernatant was analyzed, and the sulfate concentration was 96 mg / L, with a sulfate removal rate of 98.40%.

[0080] Comparative Example 1 The wastewater was the same as in Example 1, except that steps S1, S3 and S4 were omitted. 7.5 g of Ca(OH)2 was added directly to each liter of wastewater, and the pH of the reaction system naturally rose to 11.0. The mixture was stirred at 250 r / min for 10 min, allowed to stand and settle for 30 min, and the supernatant was taken for testing. The sulfate concentration in the effluent was 2200 mg / L, and the sulfate removal rate was 63.3%.

[0081] Comparative Example 2 The wastewater was the same as in Example 1, except that steps S1, S3, and S4 were omitted. 12 g of Al(OH)3 was directly added per liter of wastewater, allowing the pH of the reaction system to rise naturally to 11.0. After stirring at 250 r / min for 10 min, anionic polyacrylamide flocculant was added to aid sedimentation. Based on the wastewater volume, the flocculant dosage was 1.5 mg / L. The mixture was stirred at 100 r / min for 5 min and allowed to stand for 30 min. The supernatant was analyzed, and the sulfate concentration in the effluent was 2660 mg / L, with a sulfate removal rate of 55.7%.

[0082] The sulfate concentration and sulfate removal rate in the water after final treatment in Examples 1-5 and Comparative Examples 1-2 are summarized in Table 1 below: Table 1

[0083] As shown in Table 1, a comparison between the examples and comparative examples demonstrates that this application achieves highly efficient sulfate removal through the synergistic effect of the calcium source and the composite rare earth aluminum colloid. The method described in this application is simple to operate, has low processing costs, and achieves a sulfate removal rate of over 90%, making it suitable for treating high-concentration sulfate wastewater from mining, chemical, and other industries.

[0084] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

[0085] Although preferred embodiments have been described in this specification, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this specification.

[0086] Obviously, those skilled in the art can make various modifications and variations to this specification without departing from its spirit and scope. Therefore, if such modifications and variations fall within the scope of the claims and their equivalents, this specification is also intended to include such modifications and variations.

Claims

1. A method for treating sulfate-containing wastewater, characterized in that, Includes the following steps: Water-soluble rare earth salts and aluminum sources are mixed in water and co-hydrolyzed under the condition that the pH of the reaction system is 5.5~6.5 to obtain composite rare earth aluminum colloids. A calcium source was added to the sulfate-containing wastewater to be treated to carry out the first reaction, and the pH of the reaction system was controlled at 9.0~12.0 to obtain the first water body; The composite rare earth aluminum colloid is added to the first water body to carry out a second reaction; and Flocculant is added to the mixture after the second reaction to carry out flocculation and sedimentation, and solid-liquid separation to obtain recycled water.

2. The processing method according to claim 1, characterized in that, The water-soluble rare earth salts include rare earth chlorides and / or rare earth nitrates, and the aluminum source includes water-soluble aluminum monomer salts and / or polyaluminum compounds; and / or, The molar ratio of rare earth ions in the water-soluble rare earth salt to aluminum in the aluminum source is 1:(2~4).

3. The processing method according to claim 2, characterized in that, The rare earth ions in the water-soluble rare earth salt include one or more of yttrium, lanthanum, cerium, neodymium, and gadolinium.

4. The processing method according to claim 2, characterized in that, The aluminum source includes aluminum chloride and / or polyaluminum chloride.

5. The processing method according to claim 1, characterized in that, The calcium source includes one or more of calcium chloride, calcium oxide, and calcium hydroxide; and / or, The molar ratio of calcium in the calcium source to sulfate in the sulfate-containing wastewater is (1.0~1.7):

1.

6. The processing method according to claim 1, characterized in that, The molar ratio of rare earth ions in the composite rare earth aluminum colloid to sulfate ions in the first water body is (1~1.5):

1.

7. The processing method according to claim 1, characterized in that, The flocculant includes anionic polyacrylamide flocculant, and / or, Based on the volume of the mixed system, the dosage of the flocculant is 1 mg / L to 2 mg / L.

8. The processing method according to claim 7, characterized in that, The anionic polyacrylamide flocculant has a molecular weight of 8 million to 12 million and a degree of hydrolysis of 20% to 30%.

9. The processing method according to any one of claims 1 to 8, characterized in that, The first reaction is carried out at a stirring speed of 200 r / min to 300 r / min for 5 to 10 minutes; and / or, The second reaction is carried out at a stirring speed of 150 r / min to 200 r / min for 10 to 15 minutes; and / or, The flocculation and sedimentation process involves stirring at a speed of 100 r / min to 200 r / min for 3 to 5 minutes, followed by settling for 30 to 60 minutes.

10. The processing method according to any one of claims 1 to 8, characterized in that, The sulfate concentration in the sulfate-containing wastewater is 1000 mg / L to 10000 mg / L.